FT-IR- based metabolomics approach to characterize the α-glucosidase inhibitory activity of Salak fruit - Saleh, Mohammed S M; Siddiqui, Mohammad Jamshed Ahmad; Mat So'ad, Siti Zaiton; Khatib, Alfi (2017)
Salak fruit (Salacca zalacca (Gaertn.) Voss), locally known as snake fruit is used domestically as food and other medicinal applications in south Asia. The quality control is important for medicinal. Thus, this study was conducted to evaluate α-glucosidase inhibitory activity of Salak fruit extracts and Fourier Transform Infrared spectroscopy (FT-IR)-based fingerprinting with combination of orthogonal partial least-squares (OPLS) was applied to develop a rapid method for quality control of this fruit. Extraction with different solvent ratios of ethanol-water (100, 80, 60, 40 ,20, 0%) was used to get 36 extracts and α-glucosidase inhibitory activity of the samples were determined. The FTIR-ATR spectra of hydro-ethanolic extracts were measured in the region 600 and 4000 cm-1 at a resolution of 4 cm-1. Multivariate analysis with combination of orthogonal partial least-squares (OPLS) algorithm was used to correlate the α-glucosidase inhibitory activity of the samples with the infrared spectral data. The OPLS biplot model identified several functional groups (C=O, O-H C-O, C-N, C-H and C=C) strongly induced α-glucosidase inhibitory activity. A successful the model was validated by comparing the model intercept values with original values.